The first dung beetle retrieved from Coprinisphaeridae ichnofossils: Phanaeus violetaen. sp. (Coleoptera: Scarabaeinae) from Ecuadorian cangahua balls - Zunino, Mario (Instituto de Ecología, A.C., 2013)
A previously unknown species of dung beetle is described, related to a Coprinisphaeridae ichnofossils. Its discovery demonstrates that such structures really are fossil nests of Scarabaeinae beetles. The taxonomic and phylogenetic relationships of the new species are discussed, as well as some hypotheses about the biogeographical history of the Phanaeus chalcomelas species group to which the fossil species is assigned. A preliminary version of both the group’s track and Steiner’s areal tree is represented and compared to the phylogenetic and biographic hypotheses of recent literature.